Posthumánní poznání v díle Rosi Braidotti - Sellner, Veronika (Filosoﬁcký časopis)
Rosi Braidotti is one of the most distinctive thinkers of contemporary posthumanism. She approaches this term in an informed manner, at the same time endeavoring to redefine it and make it applicable to contemporary society, primarily through a critique of global capitalism. In the text, I will present this Italian philosopher’s concept of posthumanism, specifically focusing on an analysis of the construction of “posthuman knowledge” and the new methods of knowledge proposed by her.